2015
DOI: 10.1097/aln.0000000000000891
|View full text |Cite
|
Sign up to set email alerts
|

Minor Postoperative Increases of Creatinine Are Associated with Higher Mortality and Longer Hospital Length of Stay in Surgical Patients

Abstract: Background Surgical patients frequently experience postoperative increases in creatinine levels. The authors hypothesized that even small increases in postoperative creatinine levels are associated with adverse outcomes. Methods The authors examined the association of postoperative changes from preoperative baseline creatinine with all-cause in-hospital mortality and hospital length of stay (HLOS) in a retrospective analysis of surgical patients at a single tertiary care center between January 2006 and June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(95 citation statements)
references
References 57 publications
(74 reference statements)
2
88
2
3
Order By: Relevance
“…Postoperative AKI was defined according to the Kidney Disease: Improving Global Outcomes (KDIGO) 2012 creatinine criteria 17 , namely a 1⋅5-fold increase in serum creatinine level from preoperative baseline or an absolute 26-μmol/l increase over a period of 48 h or less within the 7 days after surgery. Additionally, separate analyses were performed to examine postoperative outcomes in patients defined as having AKI stage 1 based purely on a 26-μmol/l increase without a rise in serum creatinine from baseline of at least 50 per cent; and in patients who experienced an increase in serum creatinine of 25 per cent or more from baseline, but less than 50 per cent, within 7 days after surgery, and did not otherwise achieve the KDIGO AKI definition by an absolute 26-μmol/l increase within 48 h. The latter group has been associated with adverse outcomes in previous studies 6 . Baseline serum creatinine was taken as the most recent value available between 7 and 365 days before the day of surgery 18 ; if none was available, the value closest to 7 days before surgery was used.…”
Section: Definitionsmentioning
confidence: 88%
“…Postoperative AKI was defined according to the Kidney Disease: Improving Global Outcomes (KDIGO) 2012 creatinine criteria 17 , namely a 1⋅5-fold increase in serum creatinine level from preoperative baseline or an absolute 26-μmol/l increase over a period of 48 h or less within the 7 days after surgery. Additionally, separate analyses were performed to examine postoperative outcomes in patients defined as having AKI stage 1 based purely on a 26-μmol/l increase without a rise in serum creatinine from baseline of at least 50 per cent; and in patients who experienced an increase in serum creatinine of 25 per cent or more from baseline, but less than 50 per cent, within 7 days after surgery, and did not otherwise achieve the KDIGO AKI definition by an absolute 26-μmol/l increase within 48 h. The latter group has been associated with adverse outcomes in previous studies 6 . Baseline serum creatinine was taken as the most recent value available between 7 and 365 days before the day of surgery 18 ; if none was available, the value closest to 7 days before surgery was used.…”
Section: Definitionsmentioning
confidence: 88%
“…Recently, Liotta et al showed that small increases in serum creatinine (0–0.3 mg/dl) were significantly associated with long-term mortality, but not with short-term (1 month) mortality, in patients following cardiac surgery [24]. Kork et al revealed that minimal increases in serum creatinine (25–50% increase from baseline, value less than 0.3 mg/dl) resulted in increased in-hospital mortality and length of hospital stay in post-surgical patients [25]. Although these studies investigated the effect of small increases in serum creatinine on clinical outcomes, they are limited to specific patient populations, i.e., patients who underwent cardiac surgery or heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative AKI is generally a risk factor for mortality after different kinds of surgery. 15,16 Regarding abdominal aortic surgery, Wald et al 13 already highlighted the higher risk of mortality (after both EVAR and OAR) in the presence of AKI (OR, 11.3%). Nevertheless, we could not include early mortality in the multivariate analysis because of the small number of cases in both groups.…”
Section: Discussionmentioning
confidence: 99%